Kajian Rantai Pasok Biji Kopi (Grean Bean) Di PT Sulotco Jaya Abadi Kabupaten Tana Toraja - Riri, Sandriyani; Pakasi, Caroline Betsi Diana; Kumaat, Ribka Magdalena (Sam Ratulangi University, 2023)
This study aims to identify the coffee supply chain that occurs at PT Sulotco Jaya Abadi, Tana Toraja Regency. This research was conducted from February to August 2022. The selection of respondents was carried out using the Snowball Sampling method. The types of data used in this research are primary data and secondary data. The primary data collected was obtained directly from the results of interviews and through questionnaires which were distributed to one respondent in the company, two collecting traders, sixty five farmers. So that the total respondents in this study were 68 people. Secondary data were obtained from related agencies, namely through the Central Statistics Agency (BPS), books, the internet, journal articles, thesis articles related to this research topic. The results of this study indicate that the supply chain at PT Sulotco Jaya Abadi, Tana Toraja Regency has two sources of raw materials, namely from the company's own coffee plantations and from local farmers through collectors. PT Sulotco Jaya Abadi's supply chain product flow is in the form of Green Bean coffee beans. PT Sulotco Jaya Abadi's supply chain financial flow is using a purchase and sale transaction system, namely a cash system and interbank transfers. The supply chain information flow of PT Sulotco Jaya Abadi occurs in two directions between the actors involved in the supply chain.